Three-dimensional graphene biointerface with extremely high sensitivity to single cancer cell monitoring - Wang, Xiahua (2020)
We developed a three-dimensional biointerface of graphene-based electrical impedance sensor for metastatic cancer diagnosis at single-cell resolution. Compared with traditional impedance sensor with two-dimensional interface, the graphene biointerface mimiced the topography and somatotype features of cancer cells, achieving more comprehensive and thorough single cell signals in the three-dimensional space. At the nodes of physiological behavior change of single cell, namely cell capture, adhesion, migration and proliferation, the collected electrical signals from graphene biointerface were about two times stronger than those from the two-dimensional gold interface due to the substantial increase in contact area and significant improvement of topographical interaction between cells and graphene electrode. Simultaneous CCD recording and electrical signal extraction from the entrapped single cell on the graphene biointerface enabled to investigate multidimensional cell-electrode interactions and predict cancerous stage and pathology.